Synthesis of Dandelion—like CuO microspheres for photocatalytic degradation of reactive black-5. (24th January 2018) - Rao, Martha Purnachander; Wu, Jerry J; Syed, Asad; Ameen, Fuad; Anandan, Sambandam
Abstract: Dandelion-like CuO microspheres with the size of ∼1–2 μ m were synthesized by ultrasound method without any surfactants. The crystallinity, morphology, composition of products and optical properties were characterized by x-ray diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, energy dispersive spectrometer, Fourier transform infrared and UV–vis absorption spectroscopy. The crystal size and optical band gap of CuO nanoparticles were found to be 6.51 nm and 1.70 eV and their photocatalytic ability towards reactive black-5 was analyzed. The observed experimental results revealed that the Dandelion-like CuO microspheres possess good photocatalytic activity i.e., around 76% dye was degraded in 5 h under visible light illumination at room temperature and the degradation follows the pseudo-first order kinetics with a rate constant of 0.312 h −1 . Suitable growth mechanism was also proposed for the formation of Dandelion-like CuO microspheres.